Maturation-related adaptations in running speed in response to sprint training in youth soccer players. Issue 5 (May 2018) - Moran, Jason; Parry, Dave A.; Lewis, Ieuan; Collison, Jay; Rumpf, Michael C.; Sandercock, Gavin R.H.
Abstract: Objectives: This study investigated the effects of a previously recommended dose of sprint training (ST) in young male soccer players of differing maturity status. Design: Quasi-experimental design. Methods: Male soccer players from two professional academies were divided into Pre-PHV (Training: n = 12; Control: n = 13) and Mid-PHV (Training: n = 7; Control = 10) groups. The training groups completed 16 sprints of 20 m with 90 s recovery, once per week for 8 weeks. Results: Between-group effect sizes (ES) were substantially larger in Pre-PHV (10 m [1.54, CI: 0.74–2.23]; 20 m [1.49, CI: 0.75–2.23]; 5-10-5 [0.92, CI: 0.23–1.61]) than in Mid-PHV (10 m [−0.00, CI: −0.81 to 0.81]; 20 m [−0.12, CI: −0.93 to 0.69]; 5-10-5 [−0.41, CI: −1.22 to 0.41]). Within-group effects demonstrated a similar, though less accentuated, trend which revealed ST to be effective in both Pre-PHV (10 m [0.44, CI: −0.24 to 1.12]; 20 m [0.45, CI: −0.23 to 1.13]; 5-10-5 [0.69, CI: 0.00–1.38]) and Mid-PHV (10 m [0.51, CI: −0.38 to 1.40]; 20 m [0.33, CI: −0.56 to 1.21]; 5-10-5 [0.43, CI: −0.46 to 1.32]). Conclusions: ST, in the amount of 16 sprints over 20 m with a 90 s rest, may be more effective in Pre-PHV youths than in Mid-PHV youths.